1997
DOI: 10.1200/jco.1997.15.8.2910
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of irinotecan in patients with metastatic colorectal carcinoma.

Abstract: According to the study design, CPT-11 showed promising activity in chemotherapy-naive patients with advanced colorectal carcinoma and modest activity in patients with prior 5-FU exposure. The toxicity with this schedule appears manageable with appropriate dose modification for individual patient tolerance and an intensive loperamide regimen for the management of diarrhea. Care should be taken when treating patients with prior pelvic radiotherapy because of the increased risk of neutropenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
0
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(95 citation statements)
references
References 18 publications
4
88
0
3
Order By: Relevance
“…Phase II trials have demonstrated objective response rates of 16 -27% in pretreated patients, with stabilisation of disease in a further 40 -60% of patients (Rougier et al, 1997;Van Cutsem et al, 1999). Median overall survival rates of up to 10 months are achievable when irinotecan is used in relapsed/refractory colorectal cancer (Shimada et al, 1993;Rothenberg et al, 1996Rothenberg et al, , 1999Pitot et al, 1997;Rougier et al, 1997;Van Cutsem et al, 1999). Two European phase III trials investigating the efficacy and safety of irinotecan, following 5-FU failure in advanced colorectal cancer, have demonstrated significant improvements in survival compared with best supportive care and 5-FU (Cunningham et al, 1998;Rougier et al, 1998).…”
mentioning
confidence: 99%
“…Phase II trials have demonstrated objective response rates of 16 -27% in pretreated patients, with stabilisation of disease in a further 40 -60% of patients (Rougier et al, 1997;Van Cutsem et al, 1999). Median overall survival rates of up to 10 months are achievable when irinotecan is used in relapsed/refractory colorectal cancer (Shimada et al, 1993;Rothenberg et al, 1996Rothenberg et al, , 1999Pitot et al, 1997;Rougier et al, 1997;Van Cutsem et al, 1999). Two European phase III trials investigating the efficacy and safety of irinotecan, following 5-FU failure in advanced colorectal cancer, have demonstrated significant improvements in survival compared with best supportive care and 5-FU (Cunningham et al, 1998;Rougier et al, 1998).…”
mentioning
confidence: 99%
“…Treatment compliance for this regimen was good, with median relative DIs delivered for L-OHP, LV and 5-FU of 92%, 92% and 94%, respectively. In the preoxaliplatin era, CPT-11 was shown to be an active agent in patients with rapidly progressing colorectal cancer (Rothenberg et al, 1996), in patients refractory to 5-FU (Rougier et al, 1998) and in patients who had progressed during or shortly after 5-FU-based chemotherapy (Pitot et al, 1997). In Rothenberg's study, however, 23% of patients developed grade 4 diarrhoea and the other studies reported a high-toxicity profile with several hospital deaths attributable to multiple gastrointestinal toxicities, together with unexpected thromboembolic events (Rothenberg et al, 2001).…”
Section: Months)mentioning
confidence: 99%
“…In clinical studies CPT-11 has demonstrated single-agent activity in advanced CRC with response rates of 20-25%. 56 In combination with 5FU, CPT-11 has produced response rates of 49% for advanced CRC. 57 Furthermore, CPT-11 has demonstrated significant activity in tumours that are refractory to 5FU.…”
Section: Cpt-11 (Irinotecan)mentioning
confidence: 99%